1980
DOI: 10.1007/bf01270905
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetic and toxicodynamic studies of beryllium

Abstract: The question of dose-effect relations of berylliosis was examined by measuring the Be-concentration in blood and urine, as well as the immunological behaviour of T-lymphocytes for a group of occupationally exposed men (smaller than 8 ng Be/m3, 4-6 h daily) and a non-exposed control group. Normal values 1.0 +/- 0.4 ng Be/g(n=10) in blood and 0.9 +/- 0.5 ng Be/g(n=10) in urine were found by an optimized flameless atomic absorption spectrometry method. The corresponding values for the exposed group (n=8) showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 16 publications
(12 reference statements)
0
17
1
Order By: Relevance
“…This concentration is lower than the values of 280-1000 pg ml −1 established for humans (Paschal et al, 1998;Stiefel et al, 1980) or 1580 and 830 pg ml −1 as respectively established by Horng et al (2002) for steel production workers and for controls. In comparison with the controls, all exposed groups have, as expected, signifi cantly higher Be concentration in urine as well as for blood and all tissues analysed in this study (lung, spleen, liver and kidney).…”
Section: −1mentioning
confidence: 56%
See 2 more Smart Citations
“…This concentration is lower than the values of 280-1000 pg ml −1 established for humans (Paschal et al, 1998;Stiefel et al, 1980) or 1580 and 830 pg ml −1 as respectively established by Horng et al (2002) for steel production workers and for controls. In comparison with the controls, all exposed groups have, as expected, signifi cantly higher Be concentration in urine as well as for blood and all tissues analysed in this study (lung, spleen, liver and kidney).…”
Section: −1mentioning
confidence: 56%
“…Levels ranging from 0.28 to 1 μg L −1 were established by Paschal et al (1998) and Stiefel et al (1980) while other studies reported mean urinary Be concentrations ranging from <0.03 to 0.4 μg L −1 (Apostoli and Schaller, 2001). Stiefel et al (1980) found increased levels in the urine of smokers (2 μg L −1 compared with 0.9 μg L −1 for non smokers). However, it seems obvious that suffi cient data are not currently available to be able to propose a biological exposure index (BEI) for urinary Be.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…CBD has been observed after beryllium exposure in compliance with the air standard of 2 µg/m 3 [63][64][65][66]. Characteristic symptoms of CBD are dyspnoea on exertion, weight loss, nonproductive cough, fatigue, chest pain, anorexia, and weakness [67][68][69].…”
Section: R Klein Et Almentioning
confidence: 99%
“…Beryllium can be measured in blood and urine, but it is not known to what extent the concentration of beryllium in these fluids relates to recent or past exposure. Observations on newly exposed workers suggest that beryllium in urine may be a reflection of the current exposure (27), but it has also been reported that the urinary excretion of beryllium may remain elevated several years after the end of exposure (28,29). In persons nonoccupationally exposed, the mean concentration of beryllium in urine and blood is around 1 ,ug/L (27).…”
Section: Berylliummentioning
confidence: 99%